Crossing Boundaries - Jay Willoughby (International Institute of Islamic Thought, 2008)
On 24-25 October 2008, the thirty-seventh annual conference of the Association of Muslim Social Scientists of North America (AMSS) was held at the Harvard Divinity School, thanks to the efforts of the late Dr. Louis Cantori (an AMSS board member) and the gracious support of Dean William Graham. Given the expanding role of religion in American foreign policy and public life, the conference’s seven panels were structured around finding common ground in a religiously pluralistic world, healing inter-religious and intra-religious rifts, and using religion to promote (or at least mitigate) international conflicts. AliA. Mazrui (Binghamton University, andAMSS President) welcomed the audience and spoke of how America, the world’s “first and only universal country,” has not always welcomed non-Anglo/non-Christian immigrants. He contended that the country might be in the process of accommodating Islam, as witnessed by the Clinton administration’s hosting of iftar dinners and the Bush administration’s extension of Ramadan greetings to the Muslim American community ...